A Case Study of Sai Temple SGs & Sursame Balaji SGs, Tehsil Jhalarapatan, District Jhalawar, Rajasthan: Exploring the Spiritual and Cultural Significance of Sacred Groves in Jhalarapatan Tehsil, Rajasthan (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The sacred groves are those pieces of protected forests that have spiritual and religioussignificance. Tehsil Jhalarapatan is a typical example of the Hadoti region characterized by naturalbeauty and specific cultural heritage. Numerous sacred grove areas are found in Jhalarapatan tehsil ofJhalawar district. These sacred groves are shelter for many animals, plant species, and tribal, nomadiccommunities. All these sacred forests have been protected by tribal and nomadic groups as well as localresidents living in tehsil Jhalarapatan since long time. The present study highlights the main sacredgroves located in Jhalarapatan tehsil known for their spiritual, religious, and cultural significance.